PERUMUSAN KALENDER SYAMSI HIJRI IRAN DAN AHMADIYAH DALAM TINJAUAN AL-SIYASAH AL-SYAR’IYYAH - Musonnif, Ahmad (IAIN Tulungagung, 2021)
Calendar had a function as a regulator of community activities, both civil and religious activities. The Islamic calendar which whom established by Prophet Muhammad by adopting Lunar system also had a civil function. The Islamic calendar also had a major element to prescribe the timing of worships such as the time of fasting and Hajj. The Shamsi Hijri Calendar of Iran and the Ahmadiyya Community were calendars based on solar system which the beginning of the year starts from the Hijrah of Prophet Muhammad. The Iranian calendar dates back to ancient Persian times while the Ahmadiyya calendar is an adoption of the Gregorian calendar labeled by the symbols of Islam. Viewed from the perspective of Siyasah Shar'iyyah, the two calendars designed so each of community gets maslahat according to paradigm of each authorities. The Iranian Hijri Shamsi Calendar designed for the Iranians to keep their identity as Persians as well as to show their Islamic identity and shiáh characteristics. The Ahmadiyya calendar designed as an effort to Islamize the Gregorian calendar aside from an effort to internationalize this Jamaah and also as a symbol of relationship between Mirza Ghulam Ahmad, the founder of Ahmadiyya and Prophet Jesus Christ since Mirza Ghulam Ahmad also pronounced as Messiah as what it seems in Prophet Jesus. In the framework of al-siyasah al-Shar'yyah, the Iranian Hijri Shamsi calendar design is not as problematic as this calendar for religious purposes nor to the Ahmadiyya calendar, as both calendars were nothing more than a civil calendars.